2010
DOI: 10.4161/cbt.9.10.11433
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of PND-1186 FAK inhibitor decreases tumor growth and spontaneous breast to lung metastasis in pre-clinical models

Abstract: Tumor metastasis is a leading cause of cancer-related death. Focal adhesion kinase (FAK) is a cytoplasmic tyrosine kinase recruited to integrin-mediated matrix attachment sites where FAK activity is implicated in the control of cell survival, migration, and invasion. Although genetic studies support the importance of FAK activity in promoting tumor progression, it remains unclear whether pharmacological FAK inhibition prevents tumor metastasis. Here, we show that the FAK inhibitor PND-1186 blocks FAK Tyr-397 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
107
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 47 publications
10
107
0
Order By: Relevance
“…High levels of both FAK and Src can be indicative of poor prognosis and tumour recurrence in a variety of cancers 5 and these data have been interpreted to suggest that inhibitors of FAK may control cancer growth and progression. Indeed several reports have shown that inhibition of FAK, often in combination with the inhibition of other targets, can suppress tumour growth and metastasis [9][10][11] . In contrast, possible negative roles for FAK in tumour progression have also been reported 12,13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of both FAK and Src can be indicative of poor prognosis and tumour recurrence in a variety of cancers 5 and these data have been interpreted to suggest that inhibitors of FAK may control cancer growth and progression. Indeed several reports have shown that inhibition of FAK, often in combination with the inhibition of other targets, can suppress tumour growth and metastasis [9][10][11] . In contrast, possible negative roles for FAK in tumour progression have also been reported 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…FAK is overexpressed in many human cancer cells and has thus emerged as an anticancer target [4][5][6][7][8] . This has led to the development of FAK inhibitors although off-target effects are apparent [9][10][11] . Moreover, evidence suggests that FAK may have pleiotropic effects and some work has pointed to FAK being a negative regulator of metastasis.…”
mentioning
confidence: 99%
“…Indeed, as described above, many forms of stress may directly stimulate the function of FAK and integrin adaptors, which thus represent potential targets for chemosensitization (Ta et al, 2008;Thao le et al, 2009). This question is of special interest since the introduction of FAK inhibitors, specific Walsh et al, 2010) or not, such as some cyclooxygenase-2 inhibitors (Casanova et al, 2008).…”
Section: Functional Consequencesmentioning
confidence: 99%
“…Increasing attention to the importance of FAK activity in triggering cancer progression has elicited, and small molecule FAK inhibitors have been extensively tested to develop anti-cancer therapeutics (Roberts et al, 2008;Stokes et al, 2011;Walsh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%